Design a "Hobbyist Concept Hub" at Kinta River, Perak / Muhammad Aidil Amin Mohd Yusoff - Mohd Yusoff, Muhammad Aidil Amin (2022)
The design purpose is to encourage people to participate and fill their free time with hobby activities at concept hub/center hub. Enhance and increase social activities at Sungai Kinta Waterfront into focal point or meeting place to avoid negative activities.